ROOTING ANEW: BELONGING AND IDENTITY IN KATHARINA KAKAR’S MOVING TO GOA - Archana N. S.; Nair, Sheeba S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper titled “Rooting Anew: Belonging and Identity in Katharina Kakar’s Moving to Goa” investigates Goan’s attachment to their homeland using place attachment theory as its theoretical foundation. Katharina Kakar’s memoir, Moving to Goa tells her narrative of transitioning from displacement to finding roots, demonstrating the core elements of place attachment through her experiences in Goa. Place attachment refers to the emotional bonds people develop with particular locations through their personal experiences, memories and social relationships. It plays a vital role in shaping how People form their place-related values, sense of identity and interact with a place, which produces deep emotional connections. In Moving to Goa, Kakar investigates how various social, cultural and emotional elements create place attachment by studying traditional practices, community life and identity transformation that contribute to this bond. This paper argues that creating bonds between people and their places constitutes an essential factor in preserving cultural identity, reinforcement of community bonds and maintaining emotional wellness amidst the challenges of globalisation and urbanization.